Pascua A Yaqui Village in Arizona - Spicer, Edward H. (University of Arizona Press, 1967)
The Yaqui of Mexico were early converts to Christianity in New Spain. Yet they came to be regarded with hostility by the newly emerging Mexican government. Many Yaquis fled Mexico in the early twentieth century and established a settlement in Arizona where they resumed a peaceful existence centered around their ceremonial calendar. Edward Spicer devoted most of his professional career to the study of the Yaquis and came to be regarded as a leading authority on that tribe. At the inception of his forty years of research stands Pascua, a firsthand description of daily village life.